1996
DOI: 10.1038/ng1096-231
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a locus for familial psoriasis maps to chromosome 4q

Abstract: Psoriasis is an inflammatory skin disease that affects 2% of the population. It is characterised by red, scaly skin patches which are usually found on the scalp, elbows and knees, and may be associated with severe arthropathy. The lesions are caused by abnormal keratinocyte proliferation, and infiltration of inflammatory cells into the dermis and epidermis. The usual age of onset of psoriasis is between 15 and 30 years, although it can present at any age. Psoriasis is recognised to have a large genetic compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
2
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 12 publications
3
124
2
4
Order By: Relevance
“…21 However, some of these scans found no evidence for linkage to HLA. 15,16,20 We subsequently showed that the evidence for linkage to HLA is markedly increased when linkage disequilibrium information is taken into account. 11,12 Recently, PSORS1 has been fine-mapped to the vicinity of HLA-C by linkage disequilibrium mapping.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, some of these scans found no evidence for linkage to HLA. 15,16,20 We subsequently showed that the evidence for linkage to HLA is markedly increased when linkage disequilibrium information is taken into account. 11,12 Recently, PSORS1 has been fine-mapped to the vicinity of HLA-C by linkage disequilibrium mapping.…”
Section: Introductionmentioning
confidence: 99%
“…28 A recessive model with an estimated penetrance of 80% and a gene frequency of 0.25 (deduced from earlier studies, 6,11 ) and a dominant model with an estimated penetrance of 70% and a gene frequency of 1.3% 17 were used.…”
Section: Linkage Analysismentioning
confidence: 99%
“…Replication studies have been reported supporting the locus on 17q, 13,14 whereas other studies fail to confirm it. 15, 16 Matthews et al 17 reported a second psoriasis gene location on chromosome 4q using a dominant model with reduced penetrance. No other study has been able to confirm this locus.…”
Section: Introductionmentioning
confidence: 99%
“…2 The genetic linkage analyses presented so far also indicate several possible non-HLA gene locations, all of which have not been confirmed. [2][3][4][5][6] Two of these studies using a few large pedigrees presented data suggesting a psoriasis susceptibility locus on 17q and 4q respectively. 3,4 Trembath et al 2 recently reported a genome scan of 66 affected sib pairs in which four potential psoriasis susceptibility loci were identified, on chromosome 2p, 6p (HLA region), 8q and 20p.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Two of these studies using a few large pedigrees presented data suggesting a psoriasis susceptibility locus on 17q and 4q respectively. 3,4 Trembath et al 2 recently reported a genome scan of 66 affected sib pairs in which four potential psoriasis susceptibility loci were identified, on chromosome 2p, 6p (HLA region), 8q and 20p. Nair et al 5 confirmed the locus in the HLA region and presented two additional novel loci on chromosome 16q and 20p using 182 sib pairs in a genome-wide scan.…”
Section: Introductionmentioning
confidence: 99%